Awareness, knowledge and acceptability of HIV pre-exposure prophylaxis among women of black descent attending sexual health clinics in England: a cross-sectional survey - Patricia Williams; Franklin Odini; Cadie Hibberd; Ayo-Ola Okunwobi-Smith (Sexually Transmitted Infections, 2026)
Objectives Women of black descent in England experience a disproportionate burden of HIV but remain under-represented among users of HIV pre-exposure prophylaxis (PrEP). Evidence on PrEP awareness, knowledge and acceptability in this population is limited. This study assessed these factors among women attending National Health Service (NHS) Sexual Health clinics. Methods An exploratory cross-sectional survey was conducted at two level 3 NHS Sexual Health services in England between August 2023 and May 2024. Women aged ≥16 years who self-identified as being of black ethnicity or descent were recruited using consecutive convenience sampling. Participants received a standardised educational leaflet on HIV and PrEP, as a brief educational intervention, before completing a structured questionnaire assessing demographics, PrEP awareness and knowledge prior to education, HIV testing awareness, sexual health behaviours, perceived HIV risk and willingness to consider PrEP following education. Data were analysed descriptively. Results Sixty-four women participated. Before receiving PrEP information, 73.0% had not previously heard of PrEP, 71.4% did not know its purpose and 80.0% were unaware of how it is taken. Following educational exposure, 72.3% reported that they would consider using PrEP (‘yes’ or ‘maybe’). Inconsistent or no condom use was reported by 78.0% of participants, and 17.3% expressed concerns about partner concurrency. One-fifth (20.0%) were unaware of where HIV testing services could be accessed. Concerns about medication side effects, daily pill-taking and potential drug interactions were the most reported barriers to PrEP use. Conclusions Women of black descent attending NHS Sexual Health clinics demonstrated low awareness and knowledge of PrEP, representing a significant barrier to engagement. However, PrEP acceptability was generally favourable following brief educational exposure. Further community-based research is needed to explore wider determinants of PrEP uptake and support equitable HIV prevention strategies.